Identification of Thermo-Mechanical Properties of Natural Polymers with a Hybrid Method - TALAŚKA, Krzysztof; MALUJDA, Ireneusz (Engineering Transactions, 2016)
This article presents the results of experimental research into beech wood shearing. The applied research methodology has made it possible to obtain average values of basic strength parameters of wood: ultimate strength, yield point and the Kirchhoff's shear modulus. In order to investigate the phenomenon of wood damage resulting from shearing forces, the attempt has been made to use the hybrid method. It combines the advantages of experimental research with a detailed investigation of the phenomenon by means of FEM analysis. The wood shearing tests have been recreated in Abaqus software in order to identify the areas in wood specimens where damage stresses appear first. The article contains sample results of experimental and numerical research with their comparative evaluation.